Headache Associated With Temporomandibular Disorders Among Young Brazilian Adolescents - Franco, Ana L. [UNESP]; Fernandes, Giovana [UNESP]; Goncalves, Daniela A. G. [UNESP]; Bonafe, Fernanda S. S. [UNESP]; Camparis, Cinara M. [UNESP] (Lippincott Williams & Wilkins, 2014)
Objective:To verify whether headaches (HAs) are associated with temporomandibular disorders (TMD) in young Brazilian adolescents.Methods:From a population sample, 3117 public school children (12 to 14 y) were randomly invited to participate in this study. TMD was assessed according to the Research Diagnostic Criteria for Temporomandibular Disorders (RDC/TMD) Axis I, in addition to questions #3, #4, and #14 of Axis II history questionnaire. HAs were investigated with question #18 of RDC/TMD Axis II. Chronic TMD pain was considered as pain that has persisted for 6 months or more, as proposed by the International Association for the Study of Pain. The statistical analysis consisted of chi(2) tests, odds ratio (OR), and logistic regression models, adopting a significance level of 5%.Results:The sample included 1307 individuals (a response rate of 41.93%), and 56.8% (n=742) were girls. Overall, 330 adolescents (25.2%) were diagnosed with painful TMD and 595 (45.5%) presented with HAs. Individuals presenting with HAs were more likely to present painful TMD (OR=4.94; 95% confidence interval [CI], 3.73-6.54, P < 0.001), especially combined muscle and joint painful TMD (OR=7.58; 95% CI, 4.77-12.05, P < 0.001). HAs also increased the risk to a higher magnitude for chronic TMD pain (OR=6.12; 95% CI, 4.27-8.78, P < 0.0001). All estimated ORs remained essentially unchanged after adjusting for sex.Discussion:HAs were a potential risk factor for TMD in adolescents, and the risk was particularly higher for painful and chronic TMD. When HAs are present in young adolescents, a complete examination is strongly recommended with regard to the presence of painful TMD, and vice versa.
Keywords: adolescents; headache; temporomandibular joint disorders; epidemiology; TMD